The conceptual framework of the child's status in private international law (Adapted from a doctoral dissertation) - Hassan, Prof. Dr. Mohamed Galal; Abdullah, Shokhan Abdul Qadir (Sulaimani Journal for Humanities, 2026)
The Iraqi legislature has organized provisions for the protection of children's rights in numerous laws, according to the child's need for protection in civil, criminal, and procedural matters, and even at the international level. At the top of the legal hierarchy is the Constitution, which guarantees fundamental children's rights and stipulates the protection of motherhood and childhood. While this protection provided by Iraqi legislation is robust and organized across several laws, it does not fully guarantee the child's legal security or ensure uniform application. Therefore, it is necessary to search for protective rules for children in various legislations. Although a draft law on child protection exists, it has not yet been issued. Similarly, there are no explicit legal texts or rules for protecting children under the provisions of private international law, and consequently, no clear legal texts or rules exist to ensure their rights are safeguarded. This is what we aim to explore in this research, which is divided into two sections. The first section addresses the concept of the child and their legal status, while the second section examines the forms of legal protection for children's rights in national laws and international conventions.
Keywords: Children; legal status; legal protection; children's rights; international relations